Passive acoustic monitoring data recorded by recorder SV1013 at mooring AWI251-2 in the Weddell Sea, Southern Ocean, in 2017 - Thomisch, Karolin; Spiesecke, Stefanie; Filun, Diego; Mattmüller, Ramona; Meister, Marlene; Zwicker, Sarah; Boebel, Olaf (PANGAEA, 2025)
Passive acoustic monitoring (PAM) data were collected by recorder SV1013 of type Sono.Vault (manufactured by develogic GmbH, Hamburg, Germany) at 61.021° S, 55.9807° W, mooring AWI251-2, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from January 2017 to February 2019, passive acoustic data were collected from January 2017 to April 2017 by SV1013 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 216 m depth and scheduled to record continuously at a sample rate of 6,857 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 2+ (see the associated data processing report), deviating from Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).